Chaihu Shugan San ameliorated cognitive deficits through regulating gut microbiota in senescence-accelerated mouse prone 8 - Li, Zhiyue; Zeng, Qiang; Hu, Shengquan; Liu, Zhanyan; Wang, Shuting; Jin, Yu; Li, Limin; Ou, Hanlin; Wu, Zhengzhi (Frontiers in Pharmacology, 2023)
Background: Traditional Chinese medicines exhibit promising preventive effects on Alzheimer’s disease. Chaihu Shugan San (CSS) is a well-known traditional herbal formula whose several kinds of ingredients have the potential of ameliorating Alzheimer’s disease. The present study aimed to evaluate the effects of CSS on the microbiota–gut–brain axis and cognitive deficits of senescence-accelerated mouse prone 8 (SAMP8) mice as well as investigate the underlying mechanisms. Methods: Thirty 5-month-old SAMP8 mice were randomly divided into the model group (SAMP8), CSS low-dose treatment group (CSSL), and CSS high-dose treatment group (CSSH). Ten SAMR1 mice were used as the normal control, and ten SAMP8 mice treated with donepezil were used as the positive control of cognitive function. CSS was orally administrated to SAMP8 mice for 8 weeks. The Morris water maze test was used to evaluate cognitive function. Histological staining was used to observe neuronal injury and Aβ deposition. Transmission electron microscopy was used to observe the synaptic ultrastructure. 16S rRNA gene analysis was performed to measure the changes in intestinal microbiota. Results: The results showed that CSS significantly improved the learning function and memory deficits of aged SAMP8 mice in the Morris water maze examination. CSS ameliorated neuronal injury, synaptic injuries, and Aβ deposition in the brain of SAMP8 mice. In addition, CSS also significantly improved microbiota composition in terms of elevating Lactobacillus reuteri and decreasing Staphylococcus xylosus in the feces of aged SAMP8 mice. Conclusion: These findings suggested that CSS might have a preventive potential for cognitive deficits in aging through regulating gut microbiota, which paved the way for the application of CSS for prevention and therapeutic purposes for mild cognitive impairment as well as Alzheimer’s disease.